On the Margins of the Motherhood Discourse: Childlessness in Lithuanian Women’s Magazines during 1991–1996 - Šumskaitė, Lina; Rapolienė, Gražina (Information & Media, 2019)
Foreign scholars highlight that despite the modernization of social life, cultural attitudes towards the family are changing slowly, and women remain closely tied to the role of motherhood (McKennon Brody, Frey, 2017). The media has the power to reflect on and change the attittudes prevailing in society, thereby reducing the stigmatizing ones. Researchers discover the domination of pronatal discourse by analyzing images of childlessness, which supports parenthood in many ways, and individuals, especially women, who do not raise children and are underestimated and often stigmatized (Gibb, 2019; Grill, 2019). In order to understand the current cultural attitudes towards childless women and to analyze changes in comparison to other countries, it is important to examine them from a historical perspective. The representation of childlessness in Lithuanian media during the last decades of the 20th century was not studied yet. The scholars (Marcinkevičienė, Praspaliauskienė, 1999; Maslauskaitė 2001; 2002) who had analyzed Lithuanian women’s magazines during the late Soviet period and after the Independence in 1990 focused mainly on the representations of familial and romantic relationships. This research, based on a qualitative content analysis of 224 articles from the most popular women’s magazines of 1991–1996, showed that sex education and abortion prevention were the prevailing topics covering the lack of public knowledge about reproductive and sexual health. The aim of the media was to consolidate motherhood as the main expression of femininity within the framewok of declining birth rates; therefore, infertility and voluntary childlessness were stigmatized.